Kandungan Padatan Teruspensi dan Padatan Terlarut pada Air di Bagian Hilir Sungai Ayung, Bali - Tomtommy Haykal; Ima Yudha Perwira; I Wayan Darya Kartika (Current Trends in Aquatic Science, 2021)
This study aimed to know the amount of suspended solids and dissolved solids in the Ayung River. This study was carried out at the Downstream of Ayung River, from December 2019 to January 2020.Water sample collected from the location was analyzed for total suspended solids (TSS), total dissolved solids (TDS), temperature, pH, and DO. The result of the study showed that the amount of suspended and dissolved solid in the evening was relatively higher than that in the morning. Temporal analysis showed that there was no big difference in both parameters. In general, the water quality level in the downstream of Ayung River was belong to Class III according to the Government Regulation Number 82, released in 2001 about The Management of water quality and water pollution control.